Pemanfaatan Spreadsheet Sebagai Sarana yang Mudah Dalam Pembelajaran Fisika - B. Suprapto Brotosiswojo (Institut Teknologi Bandung, 2002)
Perhaps it never enter into our mind that spreadsheet like Excel can be used as an effective media for learning physics. This paper presents samples of the author teaching experience during the past three consecutive semesters for second and third year students in ITB. Topics like mechanics, wave and electricity can easily be simulated. Solving differential equation can be carried out by simple copy and paste on cells in the spreadsheet. The availability of rich mathematical functions for cells, graphics presentation, and programming through macro, creates an ideal learning environment. Students would not only learn how to write computer programs, but they also learn from hands on experience what they are actually doing.